(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
Sex slavery operated through the comfort women system during World War II has been a historical shame and an inconvenient truth for both the Japanese and the Korean. This study, through Nora Okja Keller’s Comfort Woman, investigates the life of a Korean character forced to become a comfort woman, arguing that domestic patriarchy and colonial patriarchy are the main institutions which transform her into a sex slave. A representation of Korean comfort women, she is exploited by the patriarchal oppression in her family and the Japanese colonial patriarchy. Her body is transformed into a commodity to sustain her family and offer comfort and pleasure to Japanese soldiers. Despite her liberation, she becomes a traumatised subject whose painful memories keep haunting her even when she relocates to the United States. Patriarchal violence in the form of sex slavery has destroyed her life and left a detrimental legacy preventing her from rebuilding a new successful life. The traumatic past causes this character and her daughter to be seen as weird Asians who are “double-othered” in the United States, a new world where they are unable to recover from profound trauma in spite of their new identity as Korean American.